Global marketing : foreign entry, local marketing, and global management - Johanson, Johny K. (Boston : McGraw-Hill Irwin, 2009)
Utilizes a three-pronged framework to organize the discussion of how to conduct global business: Foreign Entry, Local Marketing, and Global Management. This title develops the varied skills a marketing manager needs to be successful in each of these tasks. It focuses on material that is relevant to the global context
Part I: Fundamentals Chapter 1: The Global Marketing Task Chapter 2: Theoretical Foundations Chapter 3: Cultural Foundations Part II: Foreign Entry Chapter 4: Country Attractiveness Chapter 5: Export Expansion Chapter 6: Licensing, Strategic Alliances, FDI Part III: Local Marketing Chapter 7: Understanding Local Customers Chapter 8: Local Marketing in Mature Markets Chapter 9: Local Marketing in New Growth Markets Chapter 10: Local Marketing in Emerging Markets Part IV: Global Management Chapter 11: Global Marketing Strategy Chapter 12 Global Products and Services Chapter 13: Global Branding Chapter 14: Global Pricing Chapter 15: Global Distribution Chapter 16: Global Advertising Chapter 17: Global Promotion, E-Commerce, and Personal Selling Chapter 18: Organizing for Global Marketing
Includes bibliographical references and indexes.
Keywords: Export marketing -- Management; Export marketing